Use of Web 2.0 Tools in Science Education: Examining Primary School Students' Perceptions on Self-Regulation - Hacer Efe; Rabia Gül; Ünsal Umdu Topsakal (Universitas Pendidikan Indonesia, 2022)
The aim of this research is to examine the effects of Web 2.0 tools used in online education on the self-regulation perceptions of primary school fifth-grade students. For this purpose, the Sun, Earth and Moon units we processed online using Web 2.0 tools. The study was implemented in a public primary school over six weeks. The sample of the study consisted of 12 students (seven female and five male students) in the 10-11 age group. The mixed research method was used in the study. The